PAMFix, a fixative developed to enable remote platelet function testing: uses and applications - Heptinstall, Stan; Fox, Susan; May, Jane; White, Ann; Dovlatova, Natalia (Research Trends, 2015)
PAMFix is a fixative that was developed to stabilise the platelet biomarker P-selectin on activated platelets. Stabilisation of this biomarker introduced the possibility of performing measurements of platelet function remotelywhere there was no access to special equipment or technical expertise. The idea was to use PAMFix to fix the platelets after stimulating platelets in blood, after which the stabilised samples would be transported to a central laboratory for ana`lysis by flow cytometry. This would obviate the need for special equipment or technical expertise at or near the point at which the blood was collected and processed. Here we demonstrate the stability of samples of blood treated with PAMFix and describe several applications which the use of PAMFix has proved to be particularly beneficial.